A Novel Method to Measure Artificial Eye Motility. Issue 6 (November 2017) - Mourits, Daphne L.; Hartong, Dyonne T.; van Beek, Johannes H. M.; Witte, Birgit I.; Tan, H. Stevie; Moll, Annette C.
Abstract : Purpose: To measure objectively, reproducibly, and noninvasively artificial eye motility, a fundamental aspect in the (cosmetic) outcome of enucleation. Method: A gaze- and pupil-tracking system, the "iView X, " was implemented to measure horizontal eye motility. The system, with adjusted software, was tested with patients wearing 1 prosthetic eye after enucleation for retinoblastoma. Measurements were repeated 5 times in every patient and analyses were performed twice by 2 independent observers. Reproducibility was tested via linear mixed models. After the implementation of the method, more data were obtained, including more patients with a history of enucleation for the treatment of retinoblastoma for eye tracker measurement, and differences in motility percentages between implant types and sizes were analyzed via Mann-Whitney U tests. Results: The intraclass correlation coefficient of the interobserver variable in the patient test group (n = 27, 6–53 years) was 0.98 and 0.96 for measurement of left gaze and right gaze, respectively. Intraobserver variation was <0.001. In the total of 58 included patients for comparative analysis, mean difference of prosthesis motility compared with the contralateral eye in abduction was 57.1% (range 3.2–91.5%); in adduction 65.8% (range 24.0–92.0%). No statistical differences were found between the different implant types and sizes. Conclusion: Motility measurements of the prosthetic eye in comparison to the contralateral eye using the iView X system are reproducible and reliable. This is, to the authors' knowledge, the first easy applicable, noninvasive, reproducible, and commercially available instrument to evaluate prosthesis motility. With the adjusted software program (freely available on request), a similar objective measurement can be performed worldwide. The implant size or type did not influence the outcome of the motility measurement; this finding deserves additional study. Abstract : Artificial eye motility measurement can be noninvasively and reliably performed with the presented eye tracker technique, facilitating comparative motility studies.